INTERNATIONAL ASSISTANCE AND COOPERATION IN HEALTH UNDER THE INTERNATIONAL LAW REGIME: A CALL FOR RESPONSIBILITIES - Pires Terto, Angela (Revista Direitos Humanos Fundamentais, 2013)
This article examines the international assistance and cooperation (IAC) under the international law. It discusses human rights obligations regarding IAC in health taking into account international legal foundations and drawing core principles based in the right to health normative features. It also suggests that extra-territorial responsibilities should apply in order to prevent human rights violations in the context of IAC.